Mengembangkan Kecerdasan Linguistik Anak Usia Dini Melalui Metode Cerita - Nur Tanfidiyah; Ferdian Utama (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2019)
Currently, children are adapting hate speeches which come from their neighborhood as well as social media without any limitation on top of parents’ advisor. Those comprised disrespectful speech, figuring senses of violence, and imitating adult’s behavior which is not appropriate regarding their age. The situation of that notion influence children in reaching adulthood if it happens regularly. Besides, the environment and media refer to a part of an object which handling big influence towards early childhood development and growth. Children’s language development was affected in the sense of growth. Their vocabularies increase in line with what they see and listen. In addition, language is essential in accordance with interaction and relation in terms of the cognitive aspect. This research aimed to recognize children’s language development using story method in a way of literature and library study in accordance with related theories. Based on the findings, the story method was able to develop children’s linguistic intelligence in which they received many new vocabularies and increased communication skill.